Secretome Signature of Cardiopoietic Cells Echoed in Rescued infarcted Heart Proteome. (28th May 2021) - Arrell, D. Kent; Crespo-Diaz, Ruben J.; Yamada, Satsuki; Jeon, Ryounghoon; Garmany, Armin; Park, Sungjo; Adolf, Jeffrey P.; Livia, Christopher; Hillestad, Matthew L.; Bartunek, Jozef; Behfar, Atta; Terzic, Andre
Abstract: Stem cell paracrine activity is implicated in cardiac repair. Linkage between secretome functionality and therapeutic outcome was here interrogated by systems analytics of biobanked human cardiopoietic cells, a regenerative biologic in advanced clinical trials. Protein chip array identified 155 proteins differentially secreted by cardiopoietic cells with clinical benefit, expanded into a 520 node network, collectively revealing inherent vasculogenic properties along with cardiac and smooth muscle differentiation and development. Next generation RNA sequencing, refined by pathway analysis, pinpointed miR-146 dependent regulation upstream of the decoded secretome. Intracellular and extracellular integration unmasked commonality across cardio-vasculogenic processes. Mirroring the secretome pattern, infarcted hearts benefiting from cardiopoietic cell therapy restored the disease proteome engaging cardiovascular system functions. The cardiopoietic cell secretome thus confers a therapeutic molecular imprint on recipient hearts, with response informed by predictive systems profiling. Abstract : Reverse translational decoding characterized the secretome of cardiopoietic cells, a regenerative therapeutic in clinical testing. A cardiovasculogenic systems signature distinguished high from low response profiles, an imprint echoed in the restored diseased proteome. Linkage of realized outcome with secretome identity suggests paracrine centrality in regenerative fitness. Pre-intervention secretome profiling would thus inform optimized selection of regenerative biologic candidates.